OPTIMIZATION METHOD OF DYNAMIC LOAD IDENTIFICATION BASED ON GENETIC ALGORITHM - XI ZhuYou; YAN YunJu; CHANG XiaoTong (Jixie qiangdu)
Based on the response sensitivity analysis on the identification of structural dynamic load,structural dynamic load was expressed as a series of parameters. To overcome the ill-posed problem during the process,the structural dynamic input load can be determined using the optimal parameters obtained by Genetic Algorithms. In the proposed method,the dynamics inverse problem was converted into the structural dynamics analysis and calculation,this can overcome the disadvantages of illconditioned matrix inverse,accumulated error and sensitive to initial conditions,etc. The numerical simulation result shows the proposed method is feasible.